Serene - Bella, Ann Margareth C. (Animo Repository, 2023)
Serene aims to deliver practical solutions to society's sleeping difficulties by venturing into sleepwear that integrates aromatherapy through a scent pin attached to the silk top. Notably, the business supports several Sustainable Development Goals: SDG 3 - Good Health and Well-being; SDG 5, Gender Equality; and SDG 12, Responsible Consumption and Production, as they operate. Serene was founded in 2022 as a sole proprietorship by five (5) female students at De La Salle University Integrated School - Laguna since it would be optimal for a freshly formed business, entailing lower start-up costs and being easy to administer. The business went from Php 25,000 starting capital, with each member contributing Php 5,000 to gross sales of Php 79,837 as of July 12, 2023. Despite many direct competitors, Serene's product stands out as it was the first to introduce scented silk sleepwear. Digital marketing also plays a significant part in the business using Serene's customized website and social media accounts: Facebook, Instagram, and TikTok. Presently, the group is offering bigger sizes and releasing more collections to suit a broader range of customers. Other product diversifications include a new scent, scrunchy, and silk sleepwear pajama set, funded solely by Serene's earnings. All this progress was made possible by the collaborative efforts of suppliers and the hard work of Serene's key personnel, led by the owner, Ms. Angel Noraine Castillo, and the heads of Operations, Marketing, Finance, and Human Resources, namely Ms. Daniella De Torres, Ms. Anne Berlyn Blanqueza, Ms. Margarita Sophia Malabanan, and Ms. Ann Margareth Bella, respectively. It is only the beginning of something serene as the group intends to continue the business and remain committed to its mission of making good sleep accessible to Filipinos through quality, affordable, eco-friendly innovation that places importance on customers' well-being.